Creating landscapes of coexistence: Do conservation interventions promote tolerance of lions in human-dominated landscapes? - Western, G; Macdonald, D; Loveridge, A; Dickman, A (Medknow, 2019)
The range-wide decline of lions has led to their conservation becoming a top priority. Protection of free-ranging lion populations is dependent on securing space for lions but also on the ability and desire of local communities to coexist with lions. Our investigation takes a comparative and case study approach to explore the individual and societal desire to maintain current lion populations alongside communities in, or surrounding, Zimbabwe's Hwange National Park, Tanzania's Ruaha National Park, and Kenya's southern Maasailand. Using data from attitudinal questionnaire surveys, we compare the desire to maintain current lion populations as well as the prevalence and success of conservation interventions aimed at increasing human-lion coexistence. In Maasailand, 88% of the respondents expressed a desire to see current lion populations maintained, while only 42% of the respondents in Ruaha and only 5% of the respondents in Hwange expressed this desire. More respondents reported predation by lions (lion predation) on livestock in Maasailand than in Hwange; personal benefits from conservation were greatest in Maasailand; and exposure to conservation education was highest in Ruaha. The Hwange findings were confounded by Zimbabwe's political and economic climate. In Ruaha and Maasailand, communal and individual conservation benefits influenced desired changes to lion population. Once variation between sites was controlled for, twinning personal benefits and conservation education together was most likely to increase an individual's desire to see current lion populations maintained.